2016
DOI: 10.18632/oncotarget.12185
|View full text |Cite
|
Sign up to set email alerts
|

Hsp60 exerts a tumor suppressor function by inducing cell differentiation and inhibiting invasion in hepatocellular carcinoma

Abstract: Heat shock protein 60 (Hsp60), a typical mitochondrial chaperone, is associated with progression of various cancers. However, its expression and significance in hepatocellular carcinoma (HCC) remain largely unclear. In the present study, the mRNA and protein expression of Hsp60 in HCC tissues were detected by quantitative RT-PCR (n=24), western blot (n=7), and immunohistochemical staining (n=295), respectively. The correlation between Hsp60 expression and clinicopathological characteristics of HCC patient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 42 publications
2
45
1
Order By: Relevance
“…In this study, we found HSP60‐silencing in HCC cells led to inhibition of cell proliferation and promotion of cell apoptosis in vitro and in vivo. The findings were inconsistent with a previous study reporting no effects on cell proliferation and apoptosis of HCC cells with HSP60‐silencing in 2016 . The discrepancies might be due to different cell lines used or efficiencies of transfection systems.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In this study, we found HSP60‐silencing in HCC cells led to inhibition of cell proliferation and promotion of cell apoptosis in vitro and in vivo. The findings were inconsistent with a previous study reporting no effects on cell proliferation and apoptosis of HCC cells with HSP60‐silencing in 2016 . The discrepancies might be due to different cell lines used or efficiencies of transfection systems.…”
Section: Discussioncontrasting
confidence: 87%
“…However, a study in 2016 indicated significant under‐expression of HSP60 in HCCs. This study suggested that HSP60 functioned as a tumor suppressor in HCC due to its ability to induce cell differentiation and to inhibit cell invasion and migration, while no effect was found on cell proliferation and apoptosis . Given the reported conflicting roles of HSP60 in HCC, we aim to clarify this issue by more precise analysis of HSP60 expression levels in the cancerous and adjacent non‐cancerous liver tissues of HCCs.…”
Section: Introductionmentioning
confidence: 98%
“…They reported that HSP60 exerted a tumor suppressor function and that its overexpression induced HCC cell differentiation with good prognosis. 8 A previous study by Lim et al reported non-significant HSP60 difference between tumor and non-tumor HBV-related HCC specimens by immunohistochemistry and dot-immunoblotting. 38 The present study showed a highly significant expressed CAF-1 mRNA levels (urine and blood) in HCC cases compared to cirrhosis and controls (p<0.001).…”
Section: Discussionmentioning
confidence: 93%
“…42 On the other hand, Zhang et al reported that HSP60 expression was significantly correlated with serum AFP and its high expression in cancer compared to pericancer tissue was associated with better overall survival. 8 Moreover, Lim et al found that HSP60 had no relation with histopathological grading and not affecting the survival in HBV-related HCC. 38 In agreement with our study; Xu et al observed a significant positive correlation between CAF-1 expression and both tumor number and size but 40 In the present study, HSP60 mRNA in urine at cutoff 258354 RU had 85%, sensitivity and 66% specificity for HCC diagnosis, a result agreed with Abdalla and Haj-Ahmad, who found 83% sensitivity and 43% specificity for HSP60 in urine for diagnosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation